2013
DOI: 10.1111/jne.12052
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Plasma Neuroendocrine Biomarkers in Patients with Acute Ischaemic Stroke

Abstract: Inflammation and activation of the neuroendocrine systems comprise important aspects of stroke pathophysiology. The present study investigated whether baseline plasma brain natriuretic peptide (BNP), N-terminal pro-brain natriuretic peptide (NT-proBNP), cortisol and copeptin levels on admission can predict short-term outcomes and mortality after acute ischaemic stroke. The study group consisted of 189 patients who had their first acute ischaemic stroke. Plasma levels of BNP, NT-proBNP, cortisol and copeptin we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
103
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(107 citation statements)
references
References 38 publications
1
103
0
3
Order By: Relevance
“…This study measured the outcome at three months [17]. Wang measured the mRS at one month post stroke, the other two significant studies also measured the outcome at three months [16,32,36]. A study by Matsumoto whose data could not be included found a link between low D-dimer concentrations and a good outcome at discharge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study measured the outcome at three months [17]. Wang measured the mRS at one month post stroke, the other two significant studies also measured the outcome at three months [16,32,36]. A study by Matsumoto whose data could not be included found a link between low D-dimer concentrations and a good outcome at discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Both studies were independently significant. Both measured the outcome at three months [21,32]. It can be assumed that low GPT concentrations at admission predict a bad neurological outcome at three months post stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Têm sido efetuados estudos na procura de potenciais marcadores do diagnóstico de AVC, estratificação de risco e previsão de prognóstico. 31 Ainda são poucos os biomarcadores que preenchem os requisitos necessários para serem introduzidos na prática clínica. 4 Embora alguns dos marcadores demonstrem capacidade preditiva, nenhum estudo foi suficiente para validar um modelo clínico baseado na utilização destes marcadores.…”
unclassified
“…Some authors postulate that the biomarker panel (BNP, NT-proBNP, cortisol and copeptin) predicted functional outcome and death within 90 days more efficiently than the NIHSS score (16) BNP levels were found to be significantly higher in patients with larger infarcts and higher mRS scores (17). Higher BNP levels were independently associated with more proximal carotid axis occlusion, thus with larger infarct area (18) BNP levels in patients with an unfavorable outcome after 90 days and after 1 year were significantly higher than those in patients with a favorable outcome (14).…”
mentioning
confidence: 99%